METEC controlled test protocol: continuous monitoring emission detection and quantification - Bell, Clay, author; Zimmerle, Daniel, author (Colorado State University. Libraries, 2020)
This testing will assess the performance of continuous monitoring (CM) systems which perform leak detection and quantification (LDAQ) under Single-Blind controlled release testing over a range of environmental conditions and emission rates. Testing will evaluate system-level performance measures including Probability of Detection and Detection Time. Additional metrics including accuracy and precision of localization and quantification estimates will be evaluated if applicable. Due to the dependence of methods on weather conditions, testing will require an extended period, typically months, with active emission and non-emissions periods to (1) allow each Experimental Design Point to operate for an extended duration, typically hours, and (2) assess performance across a wide range of meteorological conditions.
Keywords: methane; leak detection; emission quantification; continuous emission monitor; test protocol